ANALISA KEKUATAN DAN KETAHANAN LUNTUR KAIN LORENG “INDIAN ARMY” BERBASIS STANDAR NASIONAL INDONESIA - Budhiman Adi Setyawan; Lomo Mula Tua (Bina Teknika, 2016)
“The Indian Army” is clothing camouflage used by one of mass organization in Indonesia. It has a different function than TNI camouflage’s nevertheless must passed from The SNI examination. They are thirdteen standard qualifications must be passed. Those are the wight of cloth (SNI ISO 3801 : 2010) 238.4 g/m2, the cloth construction (SNI ISO 7211-2:2010) the total of warp is 42.8 yarn/cm and woof is 24.4 yarn/cm, The yarn number of warp and woof (SNI ISO 7211-5:2010) Ne1 40.2/2 and Ne1 15, The plaiting (SNI ISO 7211-1:2010) is plat/ribstop, The stress-strain of cloth (SNI 0276:2009) (the stress of warp is 42.8 kgs and woof direction is 26.42 kgs and the strain of warp is 23,71 % and woof is 12,20 % ), The strengthness to a torn piece of cloth (SNI ISO 13937-1:2013) for the warp direction is 4,490 gms dan woof is 3,250 gms, The composition of cloth (SNI 08-0265 : 1989) the cotton is 60.2 % and the polyester is 39.8 %, Colourfastness to washing (SNI ISO 105-C06:2010) is 4 GS/SS, to crocking (SNI 0288 : 2008) is 2-3 in wet and 3-4 in dry crocking, to sweat (SNI ISO 105-E04 : 2010) is 4, Light (SNI 08-0289:1996) is 4 for BWS and catagory of dyestuff (SNI 08-0519:1989) is the dispers dyes and (SNI 08-0621:1989) is the vat dyes. “The Indian Army” passed on the twelve of standards except one that is SNI 0288:2008 (the colourfastness to crocking). The conclution that the Indian Army is not accepted yet